2023
DOI: 10.3389/fenvs.2023.1095349
|View full text |Cite
|
Sign up to set email alerts
|

The impact of urban sprawl on green total factor productivity: A spatial econometric analysis in China

Abstract: The rapid expansion of Chinese cities has led to serious urban productivity and eco-environment changes, and has therefore attracted considerable international academic attention. The main objective of this study is to investigate the theoretical mechanisms and practical effects of urban sprawl on green total factor productivity (GTFP), in order to provide a reference for optimizing the spatial layout of cities and promoting high-quality economic development. Realistic urban land area and population characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The spatial autocorrelation and convergence models were used to analyze China's evolution characteristics and spatial pattern of green development. Li and Liu (2019) analyzed the economic growth clusters in the Yangtze River Delta, Pearl River Delta, and Beijing-Tianjin-Hebei regions in China through an inefficiency model and found that resources and environment were the main factors leading to the GTFP inefficiency [41]. Amani et al (2019) considered the use of relaxation-based measurement (SBM) model transformation index in variable return on Scale (VRS) to develop MPI [42].…”
Section: Introductionmentioning
confidence: 99%
“…The spatial autocorrelation and convergence models were used to analyze China's evolution characteristics and spatial pattern of green development. Li and Liu (2019) analyzed the economic growth clusters in the Yangtze River Delta, Pearl River Delta, and Beijing-Tianjin-Hebei regions in China through an inefficiency model and found that resources and environment were the main factors leading to the GTFP inefficiency [41]. Amani et al (2019) considered the use of relaxation-based measurement (SBM) model transformation index in variable return on Scale (VRS) to develop MPI [42].…”
Section: Introductionmentioning
confidence: 99%
“…In order to explore the dynamic changes of the innovation efficiency of the cultural industry in the Yangtze River economic belt, the Malmquist index Referring to the research of relevant scholars [33]- [35], the influencing factors of the spatial econometric model are selected as sulfur dioxide emissions in exhaust gas (SDE), investment completed in industrial pollution control (IPC), per capita GDP (AGDP), patent applications of domestic applicants (NPA), total printing of books published (100 million copies) (BPG) and total import and export volume of foreign-funded enterprises (TEF).…”
Section: Innovation Efficiency Of Cultural Industry In the Yangtze Ri...mentioning
confidence: 99%
“…For example, Sun et al investigated the nonlinear effect of environmental regulation on AGTFP, and pointed out that there is a threshold effect of environmental regulation on AGTFP; that is, when the threshold interval of environmental regulation intensity is reached, its negative effect on AGTFP gradually increases [21]. Liu et al pointed out that urban expansion can significantly inhibit AGTFP in a given region, but because of the presence of spatial and geographical correlation, urban sprawl is conducive to the improvement of AGTFP in neighboring cities [22]. Ge et al proposed that registered residence urbanization and permanent urbanization can improve AGTFP by optimizing factor allocation, capital expansion, and technological spillover [23].…”
Section: Literature Reviewmentioning
confidence: 99%